The Role of Barley, Sorghum, Rice, and Maize in North African Cuisine - (:unkn) unknown (My University, 2025)
Background: Cereal-based foods have been a cornerstone of North African diets for centuries, with grains such as barley, rice, maize, and sorghum holding significant importance for food security, nutritional well-being, and cultural identity. Aims: This review systematically catalogs traditional cereal-based dishes prevalent across North Africa, specifically focusing on those derived from barley, rice, maize, and sorghum. The review further explores their profound cultural significance, nutritional value, and contemporary adaptations, thereby highlighting their potential relevance in modern dietary trends. Methods: A comprehensive literature analysis was conducted across scholarly databases such as PubMed, Scopus, and Web of Science, supplemented by an examination of relevant ethnographic and culinary texts. The search strategy incorporated both keywords and controlled vocabulary terms to identify publications spanning from 2000 to May 2024, with no language restrictions (English, Arabic, and French publications were included). The analysis specifically concentrated on the traditional recipes, cooking methods, nutritional profiles, cultural significance, and historical contexts of traditional cereal-based foods indigenous to North Africa. Results: The review elucidates the substantial diversity and versatility of traditional cereal-based dishes originating from Algeria, Morocco, Tunisia, Egypt, and Libya. These culinary preparations consistently demonstrate high nutritional value, serving as rich sources of essential nutrients such as dietary fiber, protein, and various vitamins. Furthermore, contemporary adaptations and innovative presentations of these traditional dishes present a viable pathway for their integration into health-conscious trends, making them suitable for contemporary diets. Conclusions: The findings underscore that the strategic revival and modernization of traditional cereal-based foods offer an opportunity for the dual objectives o
Keywords: African Research